Carbapenem- and colistin-resistant Enterobacterales in intensive care unit patients in Mediterranean countries, 2019 - Dos Santos, Sandra; Diene, Seydina M.; Benouda, Amina; Zerouali, Khalid; Ghaith, Doaa M.; El-Mahdy, Rasha H.; El Tayeb, Sawsan H. M.; Boutiba, Ilhem; Hammami, Adnene; Chrabieh, Remie; Daoud, Ziad; Mereghetti, Laurent; et al. (Frontiers in Microbiology, 2024)
Abstract. The colonization of patients by carbapenemase-producing Enterobacterales (CPE) has been associated with heightened mortality, especially in vulnerable individuals within intensive care units (ICUs). Our study aimed to comprehensively assess CPE prevalence among ICU patients across the Mediterranean region pre-COVID-19, conducting a multicenter prevalence study in the first quarter of 2019. Nine centers across Morocco, Tunisia, Egypt, and Lebanon voluntarily participated. We collected clinical data and rectal or fecal samples from 256 ICU patients for CPE testing. Additionally, we performed whole-genome sequencing on 40 representative CPE strains to document their molecular characteristics. Among the 256 patients, CPE was detected in 73 samples (28.5%), with prevalence varying from 3.3% to 69.0% across participating centers. We observed 13 colistin-resistant CPE strains, affecting three ICUs. Genetic analysis revealed highly diverse E. coli and K. pneumoniae strains, predominantly from international high-risk clones. Notably, blaOXA-48 and blaNDM-1 were the most prevalent carbapenemase genes. Molecular typing uncovered potential patient clusters in six centers. Significantly, longer hospital stays were associated with increased CPE carriage (p<0.001). Our study provides CPE prevalence in Mediterranean ICUs and reaffirms established CPE presence in this setting but also provides updates on the molecular diversity of CPE strains. These findings highlight the imperative of reinforcing infection control measures in the participating ICUs to curtail escalated mortality rates, and of strictly applying isolation measures around patients originating from the Mediterranean region when transferred to other healthcare institutions.